Pengaruh Studi Independent pada Kurikulum MBKM Terhadap Mahasiswa Komputer - Hanna Willa Dhany; Izzmi Aulia; Shiddiq Akbar Nugraha; Laila Hasanah; Lola Amalia (Journal Of Indonesian Social Society (JISS), 2023)
Program MBKM This of course very beneficial for student in era modern and this program should be continued. Everything just goes with Good However still just there is things Which must fixed so that the future can be much better. The University establishes a relationship or cooperation with the organization who are outside the campus for the MBKM Independent Study Program because basically MBKM is a means that is realized so that students can develop self in outside environment campus. Besides expected cooperate more, so that students get rights freedom to choose What Which they Want to capable campus give the best. And what needs to be considered is that cooperation is established long before the student's schedule to carry out the MBKM Program If you pay attention again, it will help success in the program will come. The author hopes the parties Panca Budi Development University Medan can provide a better system for program implementation MBKM related to additional information that is clearer, valid and orderly students can carry out activities more efficiently and guide writer in a manner Good so that create results Work Which more quality expected web profile Which made can beneficial can be used by continuing to periodically update the information And made the more interesting. Hopefully the Program Studies Knowledge Philosophy Unpab can take advantage of the Web Profile of this Study Program well, as a medium information to assist candidate of student Which want to look for information about the world of lectures and make it easier for them to find information Where just and anytime only via the internet.